PENGARUH MEDIA VIRTUAL FIELD TRIP TERHADAP KEMAMPUAN BERPIKIR KRITIS - Eneng Desri Handayani; Suhendar Suhendar; Billyardi Ramdhan (Jurnal Pelita Pendidikan, 2018)
This study aims to find out how students' critical thinking skills after learning using Outdoor Learning method assisted by virtual media field trip on learning biology material of coral reef ecosystem. This type of research is quasi experimental research with 2 class research population taken from class X SMA. The sample of this research was chosen by using purposive sampling technique. The research design used in this research is Nonequivalent Control Group Design. The instrument used in this study is a matter of as many as 7 test questions that each have been declared valid and reliable. Based on the data requirement test, it is known that the research data is normally distributed and the two classes have the same variance (homogeneous). From the data analysis it is known that the mean posttest grade of the experimental class with the learning using the Virtual Field Trip media aid is 70.76 and the mean posttest of the control students with the learning not using the Virtual Field Trip media is 55.23. There is a significant difference to student learning outcomes, it is proved by Z-test obtained Zcount (2.13> 1.96) then this research rejects H0 and receives H1. Thus, it can be concluded that there is influence of learning outcomes on the ability of critical thinking of students who follow the learning method using Outdoor Learning media-assisted Virtual Field Trip on the material of coral reef ecosystem. Keywords: Critical Thinking, Test Problems, Virtual Field Trip.